The Effect of The Use of Project Based Learning Models and Flip Based E-Modules on Statistics Materials on Students’ Interest and Learning Outcomes of Class XI TKJ Students at SMK Ifadah - Ria Irmawati Ningsih; RA Rica Wijayanti; Moh. Affaf (JED (Jurnal Etika Demokrasi), 2022)
This research is motivated by the students' very low interest in learning, this makes students unmotivated in the learning process. Lack of motivation to actively participate in student learning has little effect on student learning outcomes. PjBL learning model and flip-based e-module media. This is an alternative that will be tested in this study. Researchers use PjBL learning models and flip-based e-module media for alternative learning strategies that can train students' cooperation so that students can increase their interest in learning. This study was to determine whether or not the use of PjBL learning models and flip-based e-module  media on the learning interest of class XI TKJ students in SMK. The type of research used in this research is descriptive quantitative research using One group pretest – posttest research design. The results of this study indicate that there is an effect of using the PjBL model and flip-based e-module media on statistical material on student interest and learning outcomes.Penelitian ini dilatarbelakangi oleh minat belajar peserta didik yang sangat rendah,hal ini membuat siswa tidak termotivasi dalam proses pembelajaran. Kurangnya motivasi untuk berpartisipasi aktif dalam belajar siswa berpengaruh kecil terhadap hasil belajar siswa. Model pembelajaran PjBL dan Media e-modul berbasis flip. Merupakan salah satu alternatif yang akan diuji cobakan pada penelitian ini. Peneliti menggunakan model pembelajaran PjBL dan media e-modul berbasis flip untuk alternatif  strategi pembelajaran yang dapat melatih kerjasama peserta didik sehingga peserta didik dapat meningkatkan minat belajar. penelitian ini adalah untuk mengetahui ada tidaknya pengaruh penggunaan model pembelajaran PjBL dan media e-modul berbasis flip terhadap minat belajar siswa kelas XI TKJ di SMK. Jenis penelitian yang digunakan dalam penelitian ini adalah jenis penelitian deskriptif kuantitatif dengan menggunakan rancangan penelitian One group pretest – posttest. Hasil penelitian ini menjukan bahwa ada pengaruh penggunaan model PjBL dan media e-modul berbasis flip pada materi statistika terhadap minat dan hasil belajar siswa.